2021
DOI: 10.1016/j.tranon.2020.100937
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment affects exogenous sodium/iodide symporter expression

Abstract: Highlights NIS-expressing xenografts show low iodide uptake in areas exhibiting hypoperfusion. NIS subcellular localization and NIS expression is impaired under quiescent and/or hypoxic states. Proteomics and metabolomics reveal tumor microenvironment-triggered changes in proteins trafficking. Controlling microenvironmental factors is important for the efficacy of radioiodine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Real-time PCR and western blotting both indicated that the expression of NIS was significant decreased under hypoxia in the PTC cells. Castillo-Rivera et al have provided evidence that hypoxia impaired NIS expression at the plasma membrane and iodide uptake within tumors, which findings were consistent with our results [31]. To demonstrate whether YAP was involved in the regulation of NIS expression, real-time PCR and western blotting were performed in PTC cells under hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…Real-time PCR and western blotting both indicated that the expression of NIS was significant decreased under hypoxia in the PTC cells. Castillo-Rivera et al have provided evidence that hypoxia impaired NIS expression at the plasma membrane and iodide uptake within tumors, which findings were consistent with our results [31]. To demonstrate whether YAP was involved in the regulation of NIS expression, real-time PCR and western blotting were performed in PTC cells under hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…have demonstrated that the tumor microenvironment may play a role in regulation of NIS function and localization of NIS at the plasma membrane, thereby affecting the efficacy of NIS gene therapy approaches, which will have to be explored further in preclinical tumor models. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these reports suggest that HIF1-α is closely related to the pathophysiology of thyroid cancer, specifically in terms of tumor aggressiveness, progression, and metastasis with characteristics of dedifferentiation [ 48 , 52 ]. Several articles have reported the relationship between hypoxia and NIS expression [ 21 , 53 , 54 ]. Lan et al demonstrated that the overexpression of HIF1-α in thyroid cancers decreased NIS expression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lan et al demonstrated that the overexpression of HIF1-α in thyroid cancers decreased NIS expression [ 53 ]. Moreover, another article reported that the tumor microenvironment, characterized by hypoxia and quiescence, could affect NIS expression and RAI uptake in exogenous NIS-expressing cancer cells [ 21 ]. Therefore, we speculated that 3D spheroid culture is hypoxic due to increased HIF-1α expression and that this phenomenon could influence the decline in thyroid-specific proteins and thyroid transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation